Marchantiophyta and Bryophyta from the mangroves of São Paulo state, Brazil - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2008)
Mangrove vegetation has born an abundance of epiphytes which usually are omitted in studies about this ecosystem. The results of the present study include collection data and literature records about the occurrence of Marchantiophyta and Bryophyta species in the mangroves of Ubatuba, São Vicente, Praia Grande, Itanhaém, Peruíbe, Iguape and Cananéia. Nineteen families with 56 genera, and 115 species are listed. The checklist adds 43% of the 115 species of Marchantiophyta and Bryophyta, which are now know to occur in the studied mangroves of São Paulo state. Hepatics predominate in the species of Marchantiophyta and Bryophyta of these mangroves, which is very similar to species found in the “paulista” Mata Atlântica.